Komparasi Model PBL dan PjBL terhadap Peningkatan Literasi Sains Siswa Kelas V Madrasah Ibtidaiyah - Aprelliza Putri Lucki Bintari; Karimatus Saidah; Frans Aditia Wiguna (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the impact of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models on improving students' scientific literacy skills and to compare the effectiveness of both models. A quantitative approach was employed using a quasi-experimental, pretest-posttest design with two treatment groups. The sample consisted of 29 fifth-grade students (Class V-C) in the PBL group and 30 fifth-grade students (Class V-D) in the PjBL group at MIS Al Irsyad Al Islamiyyah, Kediri City. Data collection involved a 30-item scientific literacy test validated by experts, achieving a feasibility score of 79.13% and a Cronbach’s Alpha reliability coefficient of 0.871. Data were analyzed using paired-sample t-tests and independent-sample t-tests with the aid of IBM SPSS 25 software. The results indicate that the PBL model had a significant effect on improving students' scientific literacy (p < 0.001). Furthermore, a significant difference in effectiveness was observed between the two models (p = 0.016), with the PjBL group achieving a higher post-test mean score (90.43) compared to the PBL group (86.69). Thus, the Project-Based Learning model is more effective than the Problem-Based Learning model in enhancing the scientific literacy of fifth-grade students regarding the topic of alternative energy.